Development of an E-Worksheet Based on Problem-Based Learning to Improve Concept Understanding - Linda Yudha Azzahra; Aldina Eka Andriani (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Science learning in elementary schools still faces challenges in the form of low student conceptual understanding, caused by the lack of digital interactive student worksheets that can facilitate concept visualization and encourage active student involvement in the learning process. This study aimed to design, validate, and examine the effectiveness of E-Worksheet based on Problem-Based Learning to improve sixth-grade students’ understanding of Earth’s rotation and revolution at SDN Kalibanteng Kidul 03, Semarang City. This research employed a Research & Development (R&D) approach using the ADDIE model, comprising analysis, design, development, implementation, and evaluation. The participants were 22 sixth-grade students. Data were collected through interviews, observations, questionnaires, documentation, and pretest–posttest instruments. Data analysis included normality testing, the Wilcoxon Signed Rank Test, and the N-Gain test. The E-Worksheet was developed using Canva, delivered through the Liveworksheet platform, and integrated with Solar System Scope as a virtual laboratory to enhance visualization. E-Worksheet-based Problem-Based Learning consists of a cover page, identity, general information, learning activities, learning activities arranged in stages based on aspects of conceptual understanding and in line with PBL syntax, and developer profiles. Validation results from material and media experts reached 93%, indicating a very feasible category. The Wilcoxon Signed Rank Test showed a significant difference between pretest and posttest scores (Asymp. Sig. = 0.046 < 0.05). The N-Gain score of 0.30 indicates a moderate improvement in students’ conceptual understanding. These findings demonstrate that the E-Worksheet based on Problem-Based Learning is successfully developed, feasible, and moderately effective in improving students’ understanding of Earth’s rotation and revolution. This study contributes a systematic worksheet that integrates PBL syntax with digital simulations and explicit conceptual understanding, serving as a model for developing interactive problem-based digital science materials and as a reference for other science subjects.